1998
DOI: 10.1038/emm.1998.19
|View full text |Cite
|
Sign up to set email alerts
|

A variant of ornithine aminotransferase from mouse small intestine

Abstract: The ornithine aminotransferase (OAT) activity of mouse was found to be highest in the small intestine. The mitochondrial OAT from mouse small intestine was purified to homogeneity by the procedures including heat treatment, ammonium sulfate fractionation, octyl-S e p h a r o s e chromatography, and Sephadex G-150 gel filtration. Comparing to the amino acid sequence of mouse hepatic OAT, six N-terminal amino acid r e s i d u e s have been deleted in intestinal OAT. However, t h e subsequent sequence was identic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…It should be highlighted that the apparent K m for α-ketoglutarate was more than fivefold lower than that for ornithine, showing that overexpressed hOAT, like mOAT ( 24 ) , has a higher affinity for α-ketoglutarate. Thus, the highly conserved OAT DNA sequence ( 43 ) would lead to highly similar enzymic properties, in agreement with previous literature data ( 44 , 45 ) .
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…It should be highlighted that the apparent K m for α-ketoglutarate was more than fivefold lower than that for ornithine, showing that overexpressed hOAT, like mOAT ( 24 ) , has a higher affinity for α-ketoglutarate. Thus, the highly conserved OAT DNA sequence ( 43 ) would lead to highly similar enzymic properties, in agreement with previous literature data ( 44 , 45 ) .
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…Two other key enzymes that regulate small molecules were also among the dysregulated proteins: OAT and PTGS1. OAT is an ornithine aminotransferase that is involved in the intestinal synthesis of citrulline and arginine (Lim et al 1998). It is highly expressed in the villus epithelium and was downregulated at all timepoints after radiation consistent with the depletion of citrulline in jejunum and plasma that was also observed in this natural history study (Kumar, Wang et al also in this issue).…”
Section: Discussionsupporting
confidence: 83%
“…Although it is not possible to tell from the crystal structure whether the hexamer is of biological relevance or merely an effect of crystal packing, there is experimental evidence for the existence of hexamers of rat liver OAT in solution approaching crystallization conditions [61]. Assemblies of dimers or tetramers have been observed in electron microscopic studies on pig kidney OAT [62], and oligomers are detected in high concentrations of mouse liver OAT [63]. The oligomerization state seems to change the kinetic properties of the enzyme [30], and may partly explain the differences observed between tissues, although the kinetic studies performed up till now have never shown any sign of cooperation between the various subunits (the kinetics seems to be of the Michaelis Menton type, see above).…”
Section: Structure Of Oatmentioning
confidence: 99%